2018
DOI: 10.2355/isijinternational.isijint-2017-426
|View full text |Cite
|
Sign up to set email alerts
|

Grain Boundary Pop-in, Yield Point Phenomenon and Carbon Segregation in Aged Low Carbon Steel

Abstract: Nanoindentation measurements, tensile tests, and carbon concentration analyses were conducted to study yield behaviors in asreceived, aged, and prestrained low carbon steel. In aged sample, steel showed both yield point phenomenon (YPP) and grain boundary (GB) pop-ins besides initial pop-in, while steels in other two states showed no YPP and only the initial pop-in. 3-dimensional atom probe (3DAP) analysis in both as-received and aged samples showed that carbon content in the matrix decreased significantly aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…As shown in 8(f), dislocation slip and accumulation at a grain boundary can lead to dislocation transfer into or dislocation nucleation within a neighboring grain with a subsequent displacement burst. Several authors observed pop-ins resulting from such behavior 19,20 . Soer and De Hosson show for a Fe-14 wt.% Si alloy that Berkovich nanoindentation near a grain boundary leads to dislocation pile-up and transmission across the boundary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in 8(f), dislocation slip and accumulation at a grain boundary can lead to dislocation transfer into or dislocation nucleation within a neighboring grain with a subsequent displacement burst. Several authors observed pop-ins resulting from such behavior 19,20 . Soer and De Hosson show for a Fe-14 wt.% Si alloy that Berkovich nanoindentation near a grain boundary leads to dislocation pile-up and transmission across the boundary.…”
Section: Resultsmentioning
confidence: 99%
“…Shen et al . even argued that carbon segregation at grain boundaries during aging of a low-carbon steel could result in pronounced grain boundary pop-ins 20 . Thus, these pop-ins should also occur at relatively high loads, because their occurrence results from the stress field coming into contact with a grain boundary.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, some previous studies have shown discontinuous yielding after tempering or ageing [ 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. It is well accepted that discontinuous yielding is caused by unpinning of dislocation from the Cottrell atmosphere, which formed by the interaction between dislocation and interstitial atoms such as carbon and nitrogen [ 52 , 54 , 55 ]. Heat treatment could induce diffusion of interstitial atoms into the dislocation core so dislocation is pinned during deformation and able to escape from the atmosphere by reaching the upper yield point.…”
Section: Resultsmentioning
confidence: 84%
“…Strain–stress curves of the entire specimen showed dome-shaped, continuous yielding behavior ( Figure 10 ). This phenomenon could be related to high mobile dislocation density without pinning effect of carbons or precipitates [ 50 , 51 , 52 , 53 ]. On the contrary, some previous studies have shown discontinuous yielding after tempering or ageing [ 50 , 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation